2010
DOI: 10.14411/eje.2010.034
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of six microsatellite loci in the larch budmoth Zeiraphera diniana (Lepidoptera: Tortricidae)

Abstract: Abstract. Six microsatellite markers were developed for the larch budmoth Zeiraphera diniana Guénée 1845, using two enrichment protocols. The number of alleles ranged from 3 to 15 per locus and observed heterozygosities ranged from 0.09 to 0.98 for the 69 individuals genotyped. Using these markers significant genetic differentiation between one population from Poland and samples from Alpine populations in France and Switzerland (overall FST = 0.0298) was detected. However, the two Alpine samples did not differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In this study, we observed a very high number of alleles per locus (average = 13.6) compared to other Lepidoptera species; 2.2 in Helicoverpa zea [ 36 ], 3 in Hyphantria cunea [ 37 ], 4.1 in Helicoverpa armigera [ 36 ], 4.6 in Carposina sasakii [ 38 ], 4.7 in Epirrita autumnata [ 35 ], 4.7 in Plutella xylostella [ 39 ], 7.0 in Chilo suppressalis [ 40 ], 8.8 in Zeiraphera diniana [ 41 ], and 10.5 in Parnassius apollo [ 42 ]. The large number of STR markers detected (2374) in this study enabled the possibility of selection of the most highly polymorphic markers.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed a very high number of alleles per locus (average = 13.6) compared to other Lepidoptera species; 2.2 in Helicoverpa zea [ 36 ], 3 in Hyphantria cunea [ 37 ], 4.1 in Helicoverpa armigera [ 36 ], 4.6 in Carposina sasakii [ 38 ], 4.7 in Epirrita autumnata [ 35 ], 4.7 in Plutella xylostella [ 39 ], 7.0 in Chilo suppressalis [ 40 ], 8.8 in Zeiraphera diniana [ 41 ], and 10.5 in Parnassius apollo [ 42 ]. The large number of STR markers detected (2374) in this study enabled the possibility of selection of the most highly polymorphic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the microsatellite cloning efficiency in Lepidoptera was very low in previous reports (Tsuchida et al , 2003; Zhang, 2004; Endersby et al , 2005; Petenian et al , 2005; Takahashi et al , 2005; Ishiguro & Tsuchida, 2006; Delamaire et al , 2010), we did not encounter a problem with cloning efficiency. The microsatellite cloning efficiency averaged 19.75% in this study, and was highest in (AC) 15 libraries (32.92%).…”
Section: Discussionmentioning
confidence: 55%
“…Although microsatellites are the most popular molecular marker in population genetics, it is difficult and challenging to develop microsatellites for many lepidopteran insects (Delamaire et al , 2010), because microsatellite sequences usually exist in multiple copies in the genome, and have similar or almost identical flanking regions in lepidopteran genomics (Meglécz et al , 2004; Sinama et al , 2011). Mobile elements (e.g.…”
Section: Discussionmentioning
confidence: 99%